Structural Characterization of the Anti-Oxidant Activity of the 1-Cys Peroxiredoxin Prx2 from the Resurrection Plant Xerophyta Viscose - Prof. Sankashana Nanda, Mr. Subham Acharya (International Journal of Modern Agriculture, 2020)
Xerophyta viscosa (Baker) is a monocotyledonous family Vellociacea resurrection plant in South Africa, Lesotho, and Swaziland, which takes place in the summer rainfall. In open grasslands, it lives on the rocky terrain and often experiences water shortage cycles. It tolerates the loss of 95 percent of total cellular water as a resurrection plant and recovers the full metabolic competence within 3 days of rehydration. Members of this antioxidant group were previously only isolated from the monocotyledons in higher plants. Seed peroxiredoxins has been suggested to protect tissues against reactive oxygen during drying and early soaking and/or to sustain / protect during dormancy. Despite variations of grain growth in monocots and dicots, the direction of AtPer1 displayed an expression pattern similar to the dormancy-related transcript Per1 in barley during the seed production and germination. AtPer1 is established in situ as the first aleuron-specified transcript in development of Arabidopsis seeds in in-situ hybridization. It is often expressed in the embryo is the transcript. Seed expression of Per1 in an ABA-deficient mutant (aba-1) is unaltered whereas the seed expression of an ABA-insensitive mutant (abi3-1) is decreased and so AtPer1 expression is decreased. Throughout the vegetative tissue, transcript is not caused by ABA or drought as a result of stress. AtPer1 transcribed rates, however, abundance of AtPer1 transcripts is not sufficient to show dormancy in non-dormant mutants. This can be attributed to germination concentrations of the wildlife.